Efficacy of Tranexamic Acid in Pediatric Craniofacial and Orthognathic Surgery: A Meta-Analysis. Issue 1 (March 2022) - Al-Shaqsi, Sultan Z.; Senkaiahliyan, Senthujan; Forrest, Christopher R.; Der, Tara D.; Phillips, John H.
Craniofacial and orthognathic surgery are high risk procedures for surgical blood loss. Significant blood loss leads to increased rates of blood product transfusion which may be associated with increased morbidity to the patient. The use of anti-fibrinolytics such as tranexamic acid has become popular in these procedures. However, the evidence to support its use in pediatric craniofacial and orthognathic surgery is sparse. This review analyzes the current randomized control trials assessing the use of tranexamic acid in craniofacial and orthognathic surgery. The study reviewed published literature up until December 20th, 2020. Six trials were included in this analysis. Pooled data showed that patients who received tranexamic acid during craniofacial or orthognathic surgery have less blood loss compared to those in control groups (mean difference—5.47 ml/kg [CI -7.02-3.82], P value <.05). Hence, rate of blood product transfusion in patients who received tranexamic acid is lower than control group by 2.01 ml/kg (CI 95%, 1.27-2.74, P value <.05). In summary, this review showed that craniofacial and orthognathic surgery patients who receive tranexamic acid might have lower estimated blood loss and receive less volume of blood products transfusion.